UJI VALIDITAS IBFWS (IMPACT BASE FORECAST AND WARNING SERVICES) DALAM MEMPREDIKSIKAN WILAYAH YANG BERPOTENSI TERDAMPAK BANJIR DI KALIMANTAN SELATAN - Hasteti, Rimelda Yuni; Rusmayadi, Gusti; Priatmadi, Bambang Joko; Mahyudin, Idiannor (EnviroScienteae, 2024)
South Kalimantan is one of the provinces in Indonesia which has a high risk of flood disasters seen from its physical condition, which geographically is mostly located below sea level. In 2021, 11 out of a total of 13 districts and cities in South Kalimantan were affected by flooding on a large scale, which caused tens of thousands of residents to suffer losses and even lost family members. IBFWS (Impact Base Forecast and Warning Services) is present as the latest innovation from the Meteorology, Climatology and Geophysics Agency as an impact-based weather forecast information service. To determine the accuracy of the IBFWS service information, it is necessary to validate the prediction results issued by IBFWS with the actual situation. By using spatial analysis methods, it is hoped that it can describe which areas are potentially affected by flooding and continued with the calculation of the contingency table so that the accuracy value of IBFWS is obtained in predicting areas potentially affected by flooding in South Kalimantan. IBFWS validation results in predicting areas potentially affected by flooding in South Kalimantan during the rainy season range between 0.85 – 1.00 which mean 85% - 100% the IBFWS prediction results are correct, during the transition season in general is 0.77 which mean 77% the IBFWS prediction results are correct, and during the dry season it ranges between 0.92 – 1.00 which mean 92% - 100% the IBFWS prediction results are correct.